-6=(5x-12)/3

Simple and best practice solution for -6=(5x-12)/3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6=(5x-12)/3 equation:



-6=(5x-12)/3
We move all terms to the left:
-6-((5x-12)/3)=0
We multiply all the terms by the denominator
-((5x-12)-6*3)=0
We calculate terms in parentheses: -((5x-12)-6*3), so:
(5x-12)-6*3
We add all the numbers together, and all the variables
(5x-12)-18
We get rid of parentheses
5x-12-18
We add all the numbers together, and all the variables
5x-30
Back to the equation:
-(5x-30)
We get rid of parentheses
-5x+30=0
We move all terms containing x to the left, all other terms to the right
-5x=-30
x=-30/-5
x=+6

You can always share this solution

See similar equations:

| 2a+1=10 | | (2x-1)(x+17)=0 | | 1+7p+p=1 | | 3(m+5)=12 | | 10(z+1)-5(z-2)=2(z-2)+2(z-1) | | (4a-1)=-23- | | 2(m-1)=-5(4m-m) | | -6w-14=8(w-7) | | 3(2x-3)-3=3(x-2)+9 | | X-0,15x=4800 | | (x-10)=-99 | | 1.5=1.2y=5.7 | | 2=10-3(x+7)+5(1-x)+6x | | X=7x-23 | | 4b÷8=20b= | | 4b÷8=20 | | 4.7x+2-4x=7+2x+4 | | 3-x/3=9/2 | | n+22=72 | | 8w?12=?5 | | (10x+9)=(4x+1) | | x^2?7x+2=0 | | 11x5=8x-6 | | 5(3m-2)-9(5-2m)=4m+2(5m+1) | | 2x2=300 | | 5(3m-2)-9(5-2m)=4m+2(5m+1 | | 3x+4=5-9 | | 9/x=98/7 | | 3x+17=32;3 | | 5x+3=15x+7 | | 261=152-v | | 5x+3+15x+7=180 |

Equations solver categories